PERGESERAN ORIENTASI PEMIKIRAN HUKUM ISLAM KONTEMPORER (Pembaharuan Pemahaman Hukum Islam dari Legal-Eksoterik Menuju Substantif-Esoterik) - Muhyidin, Muhyidin; Supeno, Ilyas (Diponegoro Private Law Review, 2019)
ABSTACT  Islamic law is often misunderstood and misunderstood by some people. Islamic law is considered unable to provide satisfactory answers to the modern problems of humanity. An approach to understanding Islamic law is very important in understanding the law itself. Then a breakthrough in understanding and shifting orientation is needed in interpreting an absolute revelation-holy text towards an essential esoteric context.